Teaching the “acid–base” subject in biochemistry via virtual laboratory during the COVID‐19 pandemic - Avci, Filiz (Biochemistry and molecular biology education, 2022)
Virtual laboratories have started to be the leading alternative teaching tools during the Covid‐19 pandemic process. The “Acid–Base” subject is among those that form the foundations of biochemistry. Students can learn the “Acid–Base” subject in a secure environment, with remote access through the use of virtual laboratory simulations. Simulation was applied to fourth‐year undergraduate students in Turkey who want to obtain a bachelor's degree in science teaching during the present study. During the application process, the students conducted different experiments on the concepts of strong acid, strong base and pH, which are the basic concepts of biochemistry. In addition, student opinions regarding the application were also obtained. It was thus determined that the majority of the students were able to write hypotheses, test their accuracy and report the test findings correctly; a small number of students started to apply the simulations after examining them in accordance with scientific terminology. At the end of the application, the students also stated that they had fun during the application which also provided effective learning. It is recommended that classroom activity which is integrated with simulation be used in Chemistry, Biochemistry and Science Laboratory Applications courses.